2006
DOI: 10.1016/j.chembiol.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Protein Phosphatase 1 Docking Motif: Molecular Description of Binding Specificities Identifies Interacting Proteins

Abstract: The interplay between kinases and phosphatases represents a fundamental regulatory mechanism in biological systems. Being less numerous than kinases, phosphatases increase their diversity by the acquisition of a variety of binding partners, thereby forming a large number of holoenzymes. Proteins interacting with protein phosphatase 1 (PP1) often bind via a so-called docking motif to regulate its enzymatic activity, substrate specificity, and subcellular localization. Here, we systematically determined structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 25 publications
1
103
0
1
Order By: Relevance
“…Early studies suggested that most regulatory subunits contain the sequence motif RVX(F/W). More recently, systematic analysis of the docking peptides that combined biochemistry with molecular dynamics gave rise to a refined consensus sequence of (H/K/R)(A/C/H/K/M/N/Q/R/ S/T/V)(V)(C/H/K/N/Q/R/S/T)(F/W) (44). However, Sds22 binds to PP1 through a non-canonical PP1-binding motif LRR rather than the RVX(F/W) motif (29).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that most regulatory subunits contain the sequence motif RVX(F/W). More recently, systematic analysis of the docking peptides that combined biochemistry with molecular dynamics gave rise to a refined consensus sequence of (H/K/R)(A/C/H/K/M/N/Q/R/ S/T/V)(V)(C/H/K/N/Q/R/S/T)(F/W) (44). However, Sds22 binds to PP1 through a non-canonical PP1-binding motif LRR rather than the RVX(F/W) motif (29).…”
Section: Discussionmentioning
confidence: 99%
“…3b. domain, the sequence that docks at the RVXF site is KSQKW. Thus, the sequence degeneracy at the RVXF site is greater than previously anticipated (44,47), and in I-2 an Ala at the Val position can be tolerated (Fig. 3).…”
Section: Structure Of the Pp1⅐inhibitor-2 Complexmentioning
confidence: 93%
“…These subunits bind to a degenerate RVXF motif present in their interacting proteins. Binding to these regulatory subunits is regulated by phosphorylation (54,60). Several proteins, including inhibitor-1, inhibitor-2, DARPP-32, and NIPP1 (nuclear inhibitor of PP1), that block PP1 activity through tight binding have been identified (54,61).…”
Section: Phosphatases Acting On Splicing Regulatory Proteinsmentioning
confidence: 99%